Fecal carriage of ESBL and Carbapenemase-producing Enterobacteriaceae, and its associated factors among hospital and non-hospital janitors at the University of Gondar, Northwest Ethiopia: A comparative cross-sectional study - Amanuale Zayede; Yitayih Wondimeneh; Sirak Biset; Mucheye Gizachew (PLoS ONE, 2026)
Background Extended-spectrum beta-lactamase (ESBL) and carbapenemase-producing Enterobacteriaceae (CPE) pose a critical public health threat. Janitors are routinely exposed to contaminated environments and may act as a reservoir for these resistant bacteria, particularly in resource-limited settings like Ethiopia, where data on this subject are scarce. Objective The aim of this study was to assess fecal carriage rates of ESBL-PE, CPE and its associated factors among hospital and non-hospital janitors at the University of Gondar (UoG), Northwest Ethiopia. Methods A comparative cross-sectional study was conducted from June 15 to September 25, 2025, at the UoG. A total of 385 janitors (203 hospital and 182 non-hospital) were selected using stratified and simple random sampling techniques. Data on socio-demographic and associated factors were collected using a semi-structured questionnaire. Stool samples were collected aseptically and cultured on MacConkey agar. Antimicrobial resistance (AMR) patterns were determined by the Kirby-Bauer disk diffusion method following Clinical and Laboratory Standards Institute (CLSI) 2024 guidelines. The ESBL and carbapenemase production were confirmed using the combination disk and modified Carbapenem inactivation methods, respectively. Quality control was ensured by using standard reference strains. Data analysis was performed using SPSS version 27.0, employing chi-square tests and logistic regression. A p -value of <0.05 was considered statistically significant. Result Among the 385 stool samples, a total of 416 Enterobacteriaceae isolates were recovered, 229 from hospital janitors and 187 from non-hospital janitors. The overall fecal carriage rates among janitors were 83 (21.6%) for ESBL-PE and 14 (3.6%) for CPE. Hospital janitors had significantly higher carriage rate than non-hospital janitors for both ESBL-PE (28.6% vs. 13.7%, p < 0.001) and CPE (5.9% vs. 1.1%, p = 0.012), respectively. Escherichia coli was the predominant ESBL-producer. Significant risk factors identified for ESBL-PE colonization included lack of hand hygiene at home, history of antibiotic use, and urinary tract infection for hospital janitors, and age ≥ 40 years and history of non-prescription antibiotic use were for non-hospital janitors. Conclusion and recommendations This high carriage rates of ESBL-PE and CPE, identify janitors as a significant reservoir for resistant bacteria. We recommend integrating janitors into national AMR surveillance programs and strengthening infection prevention and control and antimicrobial stewardship training.